THE RELATIONSHIP BETWEEN STRATEGIC IMPROVISATION AND INNOVATIVE BEHAVIOR IN JORDAN FROM LITERARY REVIEW PERSPECTIVE - Dua’a Adnan M Abu Shariah; Kamel Mohammad AL Hawajreh (American Journals, 2024)
In the struggle between technology and high competition, business institutions seek to deal in a way that ensures adaptation and innovation to ensure their survival in the market. Hence, strategic improvisation emerged to deal with challenges and events so that there is a rapid response to all data, in addition to compatibility of business innovation in a way that suits the volatile business environment. Hence, the current study came to investigate this relationship between strategic improvisation and innovation from a theoretical perspective. To achieve the objectives of the study, the descriptive approach was adopted by systematically reviewing previous relevant literature. It reflects theories and contributions in the field within different circumstances and data. The comprehensive review study concluded that there is a positive relationship between strategic improvisation and innovation. So that companies that rely on strategic improvisation will be more innovative at all levels. Hence, the study recommends that Jordanian companies, after suffering many challenges after the Corona virus, need to employ strategic improvisation strategies in harmony with innovation in business to have added value and continue in the Jordanian business environment that suffers from many challenges represented by politics and economics.
Keywords: Strategic Agility, Organization Structure, Idea Exploration, Idea Generation, Entrepreneurship, Strategic Adaptation